2009
DOI: 10.2174/1875044300902010036
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Renal LAT2 and 4F2hc Expression by Aldosterone

Abstract: In the spontaneous hypertensive rat, overexpression of the renal Na +-independent L-amino acid transporter LAT2 is organ specific, precedes the onset of hypertension, correlates negatively with plasma aldosterone, and parallels the enhanced ability to take up L-DOPA and form renal dopamine. The present study evaluated the role of aldosterone on transcript and protein abundance of Na +-independent and Na +-dependent amino acid transporters. Na +-independent heterodimeric amino acid transporters LAT1/4F2hc, LAT2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…At the protein level, aldosterone treatment did not significantly affect LAT1 and LAT2 expression, but markedly reduced the abundance of 4F2hc, although reduced levels were not reversed by spironolactone. The decrease in LAT2 functionality (related to the decrease of 4F2hc abundance) correlated well with the reduction in urinary dopamine (96). Taken together, these results suggested that the transcript abundance of AATs is age dependent and can be modulated by aldosterone.…”
Section: Modulation Of Renal Aats In Hypertensionmentioning
confidence: 81%
See 1 more Smart Citation
“…At the protein level, aldosterone treatment did not significantly affect LAT1 and LAT2 expression, but markedly reduced the abundance of 4F2hc, although reduced levels were not reversed by spironolactone. The decrease in LAT2 functionality (related to the decrease of 4F2hc abundance) correlated well with the reduction in urinary dopamine (96). Taken together, these results suggested that the transcript abundance of AATs is age dependent and can be modulated by aldosterone.…”
Section: Modulation Of Renal Aats In Hypertensionmentioning
confidence: 81%
“…Attempts were made to determine whether treatment with aldosterone had an effect on L‐DOPA uptake and LAT2 expression in WKY and SHR PTE cells and in Madin‐Darby canine kidney epithelial cells, but no differences were observed in the treatment time frame of the study (unpublished results). On the other hand, 8‐wk‐old normotensive Wistar rats chronically treated for 8 d with aldosterone had increased renal cortical LAT2 mRNA levels with no changes in LAT1, 4F2hc, and ASCT2 transcript levels (96). The effect of aldosterone on LAT2 mRNA levels was completely prevented by spironolactone, a mineralocorticoid receptor antagonist.…”
Section: Modulation Of Renal Aats In Hypertensionmentioning
confidence: 99%
“…Thus, the regulation of transfer activities by substrates needs to be elucidated in further research. Pinho et al reported that LAT2 and 4Fhc could be downregulated by aldosterone suggesting that LAT2 participates in dopamine metabolism (Amaral et al 2008;Pinho et al 2009). In addition, it has been shown that the function of LAT2 in nervous activity regulation is controlled by steroid hormone.…”
mentioning
confidence: 99%